Bioinformatics resources and approaches for the interaction of Oryza sativa and Magnaporthe oryzae pathosystem. (6th May 2019) - Sharma, V.; Singh, V.; Katara, P.
Rice is a major cereal crop and serves as staple food for a large part of the human population of world. Rice blast, caused by Magnaporthe oryzae, is a very important disease that attacks rice, affecting its production and is of common occurrence wherever rice is grown. It is also considered as a model disease for the study of genetics and molecular pathology of host pathogen interactions. Numerous comprehensive studies on both the host and pathogen have been carried out using genomics, proteomics and bioinformatics approaches. Consequently, an enormous amount of information has been made available for researchers to carry out further work on this pathosystem. Bioinformatics has played a significant role in storage and interpretation of the data made available by various wet laboratory experiments, into useful biological information. This review presents an overview of the bioinformatics resources and approaches for the study of rice-Magnaporthe interaction.